Oleico+ sustainability in the olive mill waste management - Ribeiro, Belina (2012)
Olive oil production generates olive mill wastes estimated at 2.5 million tonnes. More than 80% of olive mill wastes consist in water. Olive mill wastewater (OMW) has environmental impacts due to its high organic load and contents in phenols, lipids and organic acids. The project Oleico +, supported by the European Program LIFE, brought together 4 Institutions from 4 European Member States to seek and select a set of environmental friendly technologies for the remediation or valorization of olive mill wastes, and to raise the awareness of olive oil stakeholders for an environmental sustainable olive mill waste management. The OLEICO + project selected eight technologies to manage olive mill wastes that may be applied to different olive mill systems and amounts of waste generated. This selection was performed with a point to grid classification of technologies sustainability and status. To access eco-sustainability several parameters were accounted, including carbon dioxide emissions, landscape impacts and bead smells. Eleven technologies were selected out of 28 inventoried. Specifically five of these technologies deal with OMW and its detoxification, and four of them produce reusable water for irrigation. Other three technologies are focused in the energetic and or agronomic valorization of olive mill wastes. Some of these technologies present positive net income values, a many of them do not require specialized workforce, but the small dimension of olive mills make the management of olive mill wastes a challenge for the industry